2012
DOI: 10.1016/j.phrs.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ischemic effects of multivalent dendrimeric A3 adenosine receptor agonists in cultured cardiomyocytes and in the isolated rat heart

Abstract: Adenosine released during myocardial ischemia mediates cardioprotective preconditioning. Multivalent drugs covalently bound to nanocarriers may differ greatly in chemical and biological properties from the corresponding monomeric agents. Here, we conjugated chemically functionalized nucleosides to poly(amidoamine) (PAMAM) dendrimeric polymers and investigated their effects in rat primary cardiac cell cultures and in the isolated heart. Three conjugates of A3 adenosine receptor (AR) agonists, chain-functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…These findings have also been confirmed in A 3 AR-overexpressing mice, where infarct size was smaller than in wild-type mice after in vivo regional IR (Shneyvays et al, 2004). Similarly, antiischemic effects have been found with positive allosteric modulators as well as with dendrimeric A 3 AR agonists (Wan et al, 2011;Du et al, 2012;Chanyshev et al, 2012).…”
Section: B Cardiovascular Systemmentioning
confidence: 53%
See 2 more Smart Citations
“…These findings have also been confirmed in A 3 AR-overexpressing mice, where infarct size was smaller than in wild-type mice after in vivo regional IR (Shneyvays et al, 2004). Similarly, antiischemic effects have been found with positive allosteric modulators as well as with dendrimeric A 3 AR agonists (Wan et al, 2011;Du et al, 2012;Chanyshev et al, 2012).…”
Section: B Cardiovascular Systemmentioning
confidence: 53%
“…Interestingly, it has been demonstrated that the PAMAM dendrimer conjugate specifically activates A 3 ARs to improve postischemic/reperfusion function in isolated mouse hearts (Wan et al, 2011). Similar results were confirmed in rat primary cardiac cell cultures and in the isolated heart where these strategically derivatized nucleosides display enhanced cardioprotective potency (Chanyshev et al, 2012). In vivo testing will now be needed to explore the effects on pharmacokinetics and tissue targeting.…”
Section: Recent Drug Development Effortsmentioning
confidence: 71%
See 1 more Smart Citation
“…The effects of three different receptor agonist-modified dendrimers in hypoxic cardiomyocytes, cardiomyocytes treated with H 2 O 2 , and ex vivo hearts subjected to ischemia-reperfusion were investigated. [60,61] Adenosine has also been encapsulated in liposomes (130 nm). [62] Compared to free adenosine, administration of the liposomal formulation prior to reperfusion in rats prolonged time in circulation and delayed degradation, showed greater accumulation in infarcted myocardium, and decreased effects on hemodynamic parameters.…”
Section: Intracellular Calcium Overloadmentioning
confidence: 99%
“…Whereas on one hand A 3 AR stimulation has been found to inhibit prostate carcinoma cells proliferation and induce cell death in myeloid and lymphoid cell lines, [10,11] it has been shown on the other dendrimers displaying multiple AR ligands. [21][22][23][24][25][26] In particular, when an A 3 ligand was conjugated to a G4 PAMAM dendrimeric core, a dramatic enhancement of both selectivity and affinity was achieved when compared to the ligand alone. [25] Gold nanoparticles were also used as platforms to modulate adenosine receptors by conjugation with both agonists and antagonists.…”
Section: Introductionmentioning
confidence: 99%